The Impact Of Artificial Intelligence On Decision-making In Light Of Technological Developments Applied - Sellali ,Boubakeur; Al-bilawi Abdul Sattar, Salih Mohammed (جامعة الوادي University of Eloued, 2025)
The study aims to analysis the impact of artificial intelligence on the decisionmaking process in light of the significant technological developments that have had a significant impact, particularly in the banking sector. To achieve this goal, we sought to review a sample of commercial banks, relying on a descriptive-analytical approach to describe the phenomenon under study and analyze its various impacts. Despite the varying degrees of impact, we sought to focus on some experiences that can be benefited from globally and regionally, the extent of AI's impact on the decision-making process. The study concluded that the use of AI technologies is one of the most important solutions used to assist in decision-making. The study also emphasized the need to adopt AI applications by developing the infrastructure that can significantly assist decision-makers in making appropriate decisions for managing commercial banks and keeping pace with technological developments in this field
مقال
Keywords: artificial intelligence; decision-making; commercial banks